Comparison of the effect of freezing on the quality of nam dokmai mango fruit - Suwicha Prakobsang; Pimpen Pornchalermpong (My University, 2018)
This study evaluated effect of freezing methods on freezing rate and physical qualities of mango flesh before and after thawing. The method of freezing included still air freezing (at -20°C), air blast freezing (at -35°C, velocity 3 m/sec) and Air Blast Combined Vacuum Freezing (at -40°C, were configured core temperature 2 level is -5°C and -10°C) until the temperature reaches -20°C. The frozen flesh were thawed and evaluated for drip loss, pH, total soluble solid, colour, texture (firmness and %firmness decrease). The results showed that Air Blast Combined Vacuum Freezing (-5°C) Quality of mango frozen after thawing did not show significant effect on pH and total soluble solid of fresh mango. The frozen mango had highest lightness (L*) and the total colour differences (ΔE) had lowest and can maintain the maximum. Therefore, it's possible to introduce air blast combined vacuum freezing techniques applied to frozen mango industry as a result of significant increases freezing rate.
Keywords: Air blast; Flesh; Lightness; Congelation; Texture (cosmology); Food Quality and Safety Studies